Synthesis and Characterization of Partially Hydrolyzed Hydrogel Based on Kappa-Carrageenan - Sadeghi, Mohammad; Shafeie, Fatemeh; Mohammadinasab, Esmat (Asian Journal of Chemistry, 2012)
The polysaccharide, kappa-carrageenan (kC) was chemically modified to achieve a novel super absorbent hydrogel via graft copolymeri-zation of methacrylamide (MAM) onto the substrate followed by alkaline hydrolysis. Ammonium persulfate (APS) and N,N'-methylene bisacrylamide (MBA) were used as a free-radical initiator and a crosslinker, respectively. The saponification reaction was carried out using aqueous solution of sodium hydroxide. Either kC-g-PMAM or hydrolyzed kC-g-PMAM was characterized by FTIR and SEM spectroscopies.